Kilka powodów, dla których opowiadamy studentom ekonomii o macierzach - Rybicki, Wojciech (Some reasons for which we tell students of economics about matrices, 2010)
In the paper we consider a role which a matrix plays in the educational process of students of economics (as a notion, a symbol of a mathematical operation as well as a numerical tool). We remind that matrices and determinants appear systematically in courses of mathematics and related subjects. They help to model and solve various significant problems of econometrics (wide sense) and operation researches. It is worth noting, howe-ver, that we make use of matrix notation in our lectures on microeconomics and macroeco-nomics. The paper initiates the series of three ―didactical‖ articles devoted to matrices. So it also plays a role of some kind of introduction to the subject. The article may be divided, in a natural way, into two parts, different in character. At the beginning we show and shortly discuss – in an informal manner – selected problems in which matrices ―work‖. The second part is quite different: it is much more formalized. The examples we describe in that seg-ment are formulated in the mathematical language. Intentionally, we have chosen elementa-ry facts taken from standard programmes of ―math‖ for students of economics. According to the plan, we collect them and place under unified label ―Matrices‖. We also have an-nounced some themes which will be considered in the following articles of the series
Didactics of Mathematics, 2010, Nr 7 (11), s. 109-126
Keywords: determinant; econometrics; matrix; micro economics; representation; theory of games